The Influence of Product Quality and Promotion on Customer Satisfaction of TikTok Shop Products in Linggar Jaya Village, Kikim Timur District - Sumiatun Sumiatun; Mujari Mujari; Darwin Kesuma (Journal of Management, Economic, and Accounting, 2026)
The purpose of this study was to determine the effect of product quality and promotion on customer satisfaction for TikTok Shop products in Linggar Jaya Village, Kikim Timur District. The variables in this study were product quality (X1), promotion (X2), and customer satisfaction (Y). The data analysis methods used were instrument testing (reliability testing, validity testing), classical assumption testing (normality testing, heteroscedasticity testing, multicollinearity testing), multiple linear regression analysis, hypothesis testing (t-test and F-test), and coefficient of determination testing. The results of the study showed that (1) product quality has a significant partial effect on customer satisfaction, as evidenced by the calculated t value > t-table (7.042 > 1.998). (2) promotion has a significant partial effect on customer satisfaction, as evidenced by the calculated t value > t-table (2.965 > 1.998). (3) Product Quality and Job Satisfaction have a significant simultaneous effect on Customer Satisfaction for TikTok Shop Products in Linggar Jaya Village, East Kikim District. This can be seen from the calculated f value > f table (66.806 > 3.991) and the significance value is smaller than the significance level (a) of 0.05 (0.000 < 0.05). .